A macroecological perspective on strategic bat conservation in the U.S. National Park Service - Thomas J. Rodhouse; Thomas E. Philippi; William B. Monahan; Kevin T. Castle (Ecosphere, 2016)
Abstract North American bat populations face unprecedented threats from disease and rapid environmental change, requiring a commensurate strategic conservation response. Protected‐area networks have tremendous potential to support coordinated resource protection, disease surveillance, and population monitoring that could become a cornerstone of 21st‐century bat conservation. To motivate this idea, we develop a macroecological perspective about bat diversity and associated conservation challenges and opportunities on U.S. National Park Service (NPS) lands. We compared occurrence records from parks against published range maps. Only 55 (19%) of parks reported as present ≥90% of the bat species expected based on range maps, highlighting the information‐gap challenge. Discrepancies suggest substantial under‐reporting and under‐sampling of bats on NPS lands; inadequate range maps and habitat specificity are implicated for some species. Despite these discrepancies, 50 species, including several range‐restricted and endangered taxa, were reported in at least one park unit, including those in the Caribbean and tropical Pacific. Species richness increased with park area at a rate (z) of ~0.1, a pattern confounded by covariation with latitude, elevation, and habitat. When accounting for these factors, richness decreased predictably at higher latitudes and increased at mid‐elevations and with greater numbers of keystone underground habitat structures (caves and mines), reflecting a strong species–energy relationship. The inclusion of covariates that represented percentage of natural vs. human‐modified (converted) landscapes and elevation range—a proxy for environmental heterogeneity—was uninformative. White‐nose syndrome (WNS) presents a tremendous challenge to the NPS: All 12 species currently known to be affected by the disease or to host the causal fungus are represented in the NPS system. One hundred and twenty‐seven NPS parks are in counties currently or likely to become WNS‐positive by 2026. All parks are expected to experience increasing temperatures in coming decades; forecasted climate change velocity is particularly high (>1 SD) for 50 parks. Seventeen parks are in the vicinity of high (>1 SD) wind turbine density. Based on these biogeographic patterns, we suggest ways to prioritize NPS parks for additional inventories, monitoring, and resource protection. Our results demonstrate how macroecology and bioinformatics together can guide strategic conservation capacity‐building among protected areas.